Dynamics of Driver Distraction: The process of engaging and disengaging - Lee, John D. (Association for the Advancement of Automotive Medicine, 2014)
Driver distraction research has a long history, spanning nearly 50 years, but intensifying over the last decade. The dominant paradigm guiding this research defines distraction in terms of excessive workload and limited attentional resources. This approach largely ignores how drivers come to engage in these tasks and under what conditions they engage and disengage from driving—the dynamics of distraction. The dynamics of distraction identifies breakdowns of interruption management as an important contributor to distraction, leading to describe distraction in terms of failures of task timing, switching, and prioritization. The dynamics of distraction also identifies disengagement in driving (e.g., mind wandering) as a substantial challenge that secondary tasks might exacerbate or mitigate. Increasing vehicle automation accentuates the need to consider these dynamics of distraction. Automation offers drivers more opportunity to engage in distractions and disengage from driving, and can surprise drivers by unexpectedly requiring drivers to quickly re-engage in driving—placing greater importance of interruption management expertise. This review describes distraction in terms of breakdowns in interruption management and problems of engagement, and summarizes how contingency, conditioning, and consequence traps lead to problems of engaging and disengaging in driving and distractions.